Aconselhamento para a prática de atividade física e estágios de mudança de comportamento dos usuários das Unidades Básicas de Saúde da cidade de Pelotas/RS - Häfele, Vítor (2016)
Purpose: To describe the prevalence of counseling to practice of physical activity and the change of behavior among users of basic health units in urban area from Pelotas, Southern Brazil. The study too verify some factors associated to counseling to physical activity. Methods: Cross-sectional study with sample of 525 people with 18 years old or more users of basic health units of urban area from Pelotas, Southern Brazil. Fifteen people were interviewed in each health unit while they were in waiting room. To verify the counseling to practice of physical activity was used the following question: “During the last year, in some time in that the Mr/Mrs was in basic health unit, did you receive counseling to practice physical activity?”. To verify the stages of change of behavior was used the questionnaire proposed by Dumith et al. published in 2008. Results: The prevalence of counseling to practice of physical activity was 35.4%. It was associated with increase of age, medical diagnosis of hipertension, continuous-use edication and the higher number of times that people were in basic health unit in the last year. The prevalences of stages of change of behavior before of counseling was: precontemplation 38.3%, contemplation 6.3%, preparation 24.0%, action 6.3% and maintenance 25.1%. After the receipt of ounseling the values changed to: 20.1%, 8.2%, 30.4%, 8.7% e 32.6%, respectively. Conclusion: The counseling to practice of physical activity must improve in basic health units. However, the counseling showed a positive influence on stages of change of behavior.